Studies on endophytic fungi associated with Thymus vulgaris and their biological activities - Marwa Ragab Hamed; Ahmed Abdelaziz Ahmed; Eman Abdullah Mohamed; Mohsen Abuelela Sayed (Cairo : Marwa Ragab Hamed, 2021)
The present study aimed to study the endophytic mycoflora of Thymus vulgaris L. which is an important aromatic and medicinal plant and assaying the antimicrobial, anticancer, total phenolic content and antioxidant activities for the different plant and fungal extracts against some pathogens with elucidation of the active components using GCMS, FTIR and HPLC. A total four morphological distinct endophytic fungi were isolated and identified. From the extracellular and cultivation mats, bioactive metabolites has been extracted using ethyl acetate to prepare the endophytic extracts, the different plant extract were prepared using ethyl acetate in one of them and methanol in the other. Antimicrobial property was assessed through disc diffusion method and DPPH assay was performed to measure the free radical scavenging activity of the extracts, on the other hand the cytotoxic potential of the fungal and plant extracts against hepatocellular carcinoma cell line (HepG2)was studied by CVS assay. The active compounds present in the extracts were identified by GC.MS, FTIR and HPLC analysis.The dominant fungal extract (A. terreus extract) showed a strong growth inhibtory effect against bacterial human pathogen and excellent free radical scavenging activity with the highest content of phenolic. It also exhibits excellent effect against hepatocellular carcinoma cells the active compounds present in the extract were identified which depicts the presence of phenolic especially carvacrol in a large amount comparing with other extracts. Its concentrations is identified by HPLC which equal 86.25 mg/g.Overall, this study suggests that extract of isolated endophytic fungi A. terreus from Thymus vulgaris can be developed as source in view of pharmaceutical context that it contains alarge concentration of carvacrol which was actualy present in Thyme. We can say that the activity of plant against different biological processes is come from its endophytic fungi activity
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany - Microbiology
Issued also as CD
Keywords: Antimicrobial; Endophytic fungi; Thymus vulgaris